Premenstrual Symptom Screening Tool: A Useful Tool for DSM-5 Premenstrual Dysphoric Disorder - Turkcapar, Mehmet Hakan; Ozdel, Kadi; Kervancioglu, Aysegul; Taymur, Ibrahim; Efe, Canan; Turkcapar, Ayse Fige; Guriz, Seher Olga (DERMAN MEDICAL PUBL, 2015)
Aim: To assess the usefulness of Premenstrual Symptoms Screening Tool (PSST) in detecting Premenstrual Dysphoric Syndrome (PMDD) and Premenstrual Syndrome (PMS) in a Turkish sample. Material and Method: One hundred and eighteen women were included in the study. Participants were menstruating women, between the ages of 18 and 49 years who work in various departments of Diskapi Yildirim Beyazit Teaching and Research Hospital. Sociodemographic data collection form, PSST, and Symptom Check List (SCL-90-R) were given to the participants, filled out by participants and checked out by researchers. Participants were divided into three groups (i.e., women with subthreshold premenstrual symptoms, women with PMDD, and women with PMS) according to the scores they get on the PSST. These groups were compared according to PSST scores and SCL-90-R scores. Results: Internal consistency was excellent (Cronbach alpha=0.928) for the items of the tool. In this sample, the prevalence of the PMDD and PMS were 15.2 % (n=18) and 32.2 % (n=38) respectively. When we compare the scores on SCL-90-R sub-scales there were significant differences between the PMDD, PMS, and women with subthreshold groups. Besides there were significant differences for the three groups in terms of percentages of women who reported moderate to severe symptoms on the four items that are essential to PMDD diagnosis. Discussion: Premenstrual Symptoms Screening Tool is a useful tool to detect candidates for PMDD and moderate to severe PMS.
Keywords: Premenstrual Syndrome; Diagnosis; Screening